Health related quality of life among the elderly: a population-based study using SF-36 survey Qualidade de vida relacionada à saúde em idosos, avaliada com o uso do SF-36 em estudo de base populacional - Margareth Guimarães Lima; Marilisa Berti de Azevedo Barros; Chester Luiz Galvão César; Moisés Goldbaum; Luana Carandina; Rozana Mesquita Ciconelli (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
As life expectancy continues to rise, one of the greatest challenges of public health is to improve the quality of later years of life. The aim of this present study was to analyze the quality of life profile of the elderly across different demographic and socioeconomic factors. A cross-sectional study was carried out in two stages, involving 1,958 individuals aged 60 years or more. Health related quality of life (HRQOL) was assessed using the SF-36 questionnaire. The lowest scores were found among measures for vitality, mental health and general health and the highest among factors including social functioning and role limitations due to emotional and physical factors. HRQOL was found to be worse among women, in individuals at advanced ages, those who practiced evangelical religions and those with lower levels of income and schooling. The greatest differences in SF-36 scores between the categories were observed in functional capacity and physical factors. The results suggest that healthcare programs for the elderly should take into account the multi-dimensionality of health and social inequalities so that interventions can target the most affected elements of HRQOL as well as the most vulnerable subgroups of the population. Com o aumento da esperança de vida, a melhoria da qualidade de vida dos anos conquistados passou a ser um dos maiores desafios da saúde pública. O objetivo deste estudo foi avaliar a qualidade de vida relacionada à saúde (QVRS) de idosos do sudeste brasileiro segundo fatores demográficos e sócio-econômicos. O estudo transversal, de base populacional, incluiu 1.958 indivíduos com 60 anos ou mais. A QVRS foi avaliada com o instrumento SF-36. As menores médias de escores foram observadas nos domínios de vitalidade, saúde mental e estado geral de saúde, e as mais altas em aspectos emocionais, sociais e físicos. Apresentaram pior QVRS os idosos do sexo feminino, de idade mais avançada, com menor nível de renda, menor escolaridade e de religião evangélica. As maiores diferenças de escores entre os subgrupos sócio-demográficos foram observadas nos domínios de capacidade funcional e aspectos físicos. Os resultados apontam a necessidade dos programas de saúde levarem em conta a multidimensionalidade da saúde e as significativas desigualdades sociais presentes, de forma a priorizar os componentes mais comprometidos da QVRS e os subgrupos populacionais mais vulneráveis.